2017
DOI: 10.1101/149633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

tDCS changes in motor excitability are specific to orientation of current flow

Abstract: Measurements and models of current flow in the brain during transcranial Direct Current Stimulation (tDCS) indicate stimulation of regions in-between electrodes. Moreover, the cephalic cortex result in local fluctuations in current flow intensity and direction, and animal studies suggest current flow direction relative to cortical columns determines response to tDCS. Here we test this idea by measuring changes in cortico-spinal excitability by Transcranial Magnetic Stimulation Motor Evoked Potentials (TMS-MEP)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…It is to be expected that in the 0° conditions medial-lateral components will be larger than for the 180° condition. This does not diminish the validity of our findings as the direction of the electric field with respect to neural elements is most important for TES physiological effects 35,36 . Thus, differences in one electric field component across stimulation conditions are important to document and control for.…”
Section: Discussionsupporting
confidence: 49%
“…It is to be expected that in the 0° conditions medial-lateral components will be larger than for the 180° condition. This does not diminish the validity of our findings as the direction of the electric field with respect to neural elements is most important for TES physiological effects 35,36 . Thus, differences in one electric field component across stimulation conditions are important to document and control for.…”
Section: Discussionsupporting
confidence: 49%
“…Except for the same scale (ie, mm) SCD and CT had, the vector‐like properties of SCD, including: (a) direction: SCD is a line starting from the point on the scalp and ending at the point on cerebral cortex and (b) magnitude: the measure of SCD representing the length of the line, also have profound impact on the modeling of tDCS. For instance, recent evidence confirmed that the directionality (or orientation) of the current injection can critically influence the field potential of the targeted region during transcranial electrical stimulation . Therefore, region‐specific SCD not only reflects the individual morphometric features, but also provides a useful and dynamic parameter to optimize the therapeutic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent evidence confirmed that the directionality (or orientation) of the current injection can critically influence the field potential of the targeted region during transcranial electrical stimulation. 34,35 Therefore, region-specific SCD not only reflects the individual morphometric features, but also provides a useful and dynamic parameter to optimize the therapeutic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Rawji et al (2018) studied the excitability changes using two electrode montages that produced EFs approximately in the PA and ML directions (left M1, 1 mA, 10 min, FDI muscle, N=15); the depth component was not reported. They found that the EF in the PA direction modulated the MEPs, decreasing the excitability, while the EF in the ML direction did not (Rawji et al, 2018). The results of experiment 2 are in line with these findings, except that the effective component was E D , not E PA .…”
Section: Which Sites Are Affected By Ef?mentioning
confidence: 99%
“…We first performed an exploratory sham-controlled motor cortical TDCS study and individually calculated the EFs in all our subjects. As the effects of TDCS are sensitive to the field direction (Rawji et al, 2018), we analysed all three orthogonal components of the EF. To find which cortical sites are potentially affected by the EF, we decided to use partial least squares (PLS) regression (Geladi and Kowalski, 1986;Wold et al, 2001), which is an effective method for finding relationships between dependent variables (here: MEP amplitude) and a large number of collinear predictor variables (here: EF in the cortex).…”
Section: Introductionmentioning
confidence: 99%